2015
DOI: 10.2754/avb201584040327
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic effects of FABP4 and SCD genes on intramuscular fatty acid profiles in longissimus muscle from two cattle breeds

Abstract: The aim of this study was to evaluate the polymorphic effects of two single nucleotide polymorphisms (SNPs) of fatty acid binding protein (FABP4) and stearoyl-CoA desaturase (SCD) genes on intramuscular fatty acid profiles in the longissimus muscle in two cattle breeds. Two previously reported SNPs of bovine FABP4 (7516G>C) and SCD (878C>T) were in turn assessed for their associations with intramuscular fatty acid profiles from the upper sirloin cuts of Aberdeen Angus and Blonde d'Aquitaine cattle. In total, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…They concluded that SCD is one of the causes of genotype variation [200]. In contrast, SCD (878C>T) SNP was observed to have no association with FA profile in upper sirloin cuts of Aberdeen Angus and Blonde d'Aquitaine cattle [112].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 98%
See 4 more Smart Citations
“…They concluded that SCD is one of the causes of genotype variation [200]. In contrast, SCD (878C>T) SNP was observed to have no association with FA profile in upper sirloin cuts of Aberdeen Angus and Blonde d'Aquitaine cattle [112].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 98%
“…Beef fat is primarily categorized into three; subcutaneous, intermuscular and intramuscular fat [112]. Saturated FA (SFA) whose levels are high in ruminant meat due to hydrogenation of dietary unsaturated FA in the rumen, are associated with health risks such as coronary heart disease [113,114], although this association remains controversial [115,116].…”
Section: Meat Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations